2022
DOI: 10.29321/maj.10.000706
|View full text |Cite
|
Sign up to set email alerts
|

Potential Protective Role of Probiotic Strains of lactobacilli Against Pesticide Toxicity

Abstract: Lactic acid bacteria (LAB) are commonly associated with agricultural produces like cereals, fruits, and vegetables. Probiotic lactobacilli are the potential microbes to reduce unavoidable pesticide absorption besides their ability to degrade pesticides in humans and wildlife. The present study aimed to evaluate the strains Lactobacillus plantarum Pb3, Lactobacillus acidophilus Pc1 and Lactobacillus lactis Pt4 for their antioxidant ability and tolerance to simulated gastric and intestinal juice to understand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In recent years, both in vitro and in vivo studies have indicated that the antioxidant properties of probiotics are mediated by reducing oxidative damage and the ROS rate in human cells 31,55 . Based on our results, exposure to CPF significantly altered renal and testicular antioxidant enzyme capacity that, of course, was completely blocked by treatment with L. casei , L. rhamnosus and L. plantarum .…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…In recent years, both in vitro and in vivo studies have indicated that the antioxidant properties of probiotics are mediated by reducing oxidative damage and the ROS rate in human cells 31,55 . Based on our results, exposure to CPF significantly altered renal and testicular antioxidant enzyme capacity that, of course, was completely blocked by treatment with L. casei , L. rhamnosus and L. plantarum .…”
Section: Resultssupporting
confidence: 65%
“…53,54 In recent years, both in vitro and in vivo studies have indicated that the antioxidant properties of probiotics are mediated by reducing oxidative damage and the ROS rate in human cells. 31,55 Based on our results, exposure to CPF significantly altered renal and testicular antioxidant enzyme capacity that, of course, was completely blocked by treatment with L. casei, L. rhamnosus and L. plantarum. Previous experimental and clinical studies have emphasized that probiotic supplements have the potential to improve antioxidant capacity in diabetic patients and rats by increasing SOD activity.…”
Section: Effects Of Probiotics On Antioxidant Markers In Cpf-treated ...mentioning
confidence: 69%
See 2 more Smart Citations